PENGARUH PELATIHAN, IKLIM KERJA DAN PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA KARYAWAN PT. GMF AEROASIA, Tbk (Studi Kasus Pada Unit Engine Maintenance) - Prakoso, Kukuh; Djati, S. Pantja (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The development of MRO (Maintenance Repair and Overhaul) business in the global era the human resources becomes one of the important assets in creating competitive added value. PT. GMF AeroaAsia, Tbk. through Human Centric Strategy traits their people as assets in transforming their business therefore employee retention by increasing job satisfaction to be important. This study aims to examine and analyse the effect of training, working climate, and career development on employee job satisfaction at Engine Maintenance unit. This research type is quantitative with the survey method using questionnaires to the permanent employee population, using Proportional stratified random sampling technique, with a total sample of 133 respondents. The analytical method used multiple linear regression. The research results show that training has significant positive effect on employee job satisfaction, work climate has significant positive effect on employee job satisfaction, and career development has significant positive effect on employee job satisfaction, and simultaneously training, work climate and career development together have significantly positive effect on employee job satisfaction. This research suggests to the company to improve employee job satisfaction through training that can improve employee's behaviour in their work, support superiors and colleagues in supervision process, and implement institutional career management that gives employees the opportunity to develop themselves and improve their career